Hierarchical N-rich carbon sponge with excellent cycling performance for lithium-sulfur battery at high rates - Zhen, Mengmeng (2020)
Lithium-sulfur batteries (LSBs) are receiving extensive attention because of their high theoretical energy density. However, practical applications of LSBs are still hindered by their rapid capacity decay and short cycle life, especially at high rates. Herein, a highly N-doped (≈13.42 at %) hierarchical carbon sponge (HNCS) with strong chemical adsorption for lithium polysulfide is fabricated through a simple sol-gel route followed by carbonization. Upon using the HNCS as the sulfur host material in the cathode and an HNCS-coated separator, the battery delivers an excellent cycling stability with high specific capacities of 424 and 326 mA h g-1 and low capacity fading rates of 0.033 % and 0.030 % per cycle after 1000 cycles under high rates of 5 and 10 C, respectively, which are superior to those of other reported carbonaceous materials. These impressive cycling performances indicate that such a battery could promote the practical application prospects of LSBs.